The Motivational Factor for the Development of Speaking Skills in the EFL Ninth Graders at Luis Fernando Vivero School - Posorja. - Rodríguez Suarez, Mayte Henryette (2024)
This research work is a descriptive study regarding motivational factors affecting speaking development in ninth graders at Luis Fernando Vivero School. This project studied 45 students and 3 English teachers. This project used a mixed methods focus since it used a survey and an interview to obtain quantitative and qualitative results to gather the opinions of the students and teachers. Once the analysis concluded, some difficulties came out like the lack of motivation, lack of interest in learning a foreign language, and lack of pedagogical strategies designed by the teachers. Finally, as a proposal, the researcher created a repository webpage where teachers would find exercises for using and developing speaking skills in ninth-grade students.